Failed to return : mysteries of the air 1939-45 - Nesbit, Roy Conyers (Patrick Stephens Limited, 1988)
When an aircraft fails to return, there is usually an element of mystery that shrouds its fate. Some of these stories concern public figures, was it really Ruldolph Hess who landed in Scotland, or as others maintain an imposter. What caused the death of Amy Johnson, was Glen Miller really in the aircraft that disappeared in fog on the way to Paris, or other stories that concern the less famous. What was the story behind the Wellington N2980 found in Loch Ness, what happened to the Beaufort L4463?